A new application of high-efficient silver salts-based photocatalyst under natural indoor weak light for wastewater cleaning. (15th September 2015) - Hua, Xia; Teng, Fei; Zhao, Yunxuan; Xu, Juan; Xu, Chuangye; Yang, Yang; Zhang, Qiqi; Paul, Shashi; Zhang, Yi; Chen, Mindong; Zhao, Xudong
Abstract: As a high-quantum-efficiency photocatalyst, the serious photo-corrosion of silver phosphate (Ag3 PO4 ), limits the practical applications in water purification and challenges us. Herein, Ag3 PO4 is found to have a high stability under natural indoor weak light irradiation, suggesting that we can employ it by adopting a new application strategy. In our studies, rhodamine B (RhB, cationic dye), methyl orange (MO, anionic dye) and RhB–MO mixture aqueous solutions are used as the probing reaction for the degradation of organic wastewater. It is found that RhB, MO and RhB–MO can be completely degraded after 28 h under natural indoor weak light irradiation, indicating that multi-component organic contaminants can be efficiently degraded by Ag3 PO4 under natural indoor weak light irradiation. The density of natural indoor weak light is measured to be 72cd, which is merely one-thousandth of 300 W xenon lamp (68.2 × 10 3 cd). Most importantly, Ag3 PO4 shows a high stability under natural indoor weak light irradiation, demonstrated by the formation of fairly rare Ag. Furthermore, we also investigate the influence of inorganic ions on organic dyes degradation. It shows that the Cl − and Cr 6+ ions with high concentrations in wastewater have significantly decreased the degradation rate. From the viewpoint of energy saving and stability, this study shows us that we can utilize the Ag-containing photocatalysts under natural indoor weak light, which could be extended to indoor air cleaning process. Graphical abstract: Highlights: Simulated wastewater is degraded under indoor weak light irradiation by Ag3 PO4 . Ag3 PO4 shows a high stability under indoor weak light irradiation. Ag3 PO4 can be applied in practice under natural indoor weak light.